Fluorescence‐Labeled Bis‐benzamidines as Fluorogenic DNA Minor‐Groove Binders: Photophysics and Binding Dynamics. Issue 4 (21st November 2014) - Bordello, Jorge; Sánchez, Mateo I.; Vázquez, M. Eugenio; Mascareñas, José L.; Al‐Soufi, Wajih; Novo, Mercedes
Abstract In recent decades there has been great interest in the design of highly sensitive sequence‐specific DNA binders. The eligibility of the binder depends on the magnitude of the fluorescence increase upon binding, related to its photophysics, and on its affinity and specificity, which is, in turn, determined by the dynamics of the binding process. Therefore, progress in the design of DNA binders requires both thorough photophysical studies and precise determination of the association and dissociation rate constants involved. We have studied two bis‐benzamidine (BBA) derivatives labeled by linkers of various lengths with the dye Oregon Green (OG). These fluorogenic binders show a dramatic fluorescence enhancement upon binding to the minor groove of double‐stranded (ds) DNA, as well as significant improvement in their sequence specificity versus the parent BBA, although with decreased affinity constants. Detailed photophysical analysis shows that static and dynamic quenching of the OG fluorescence by BBA through photoinduced electron transfer is suppressed upon insertion of BBA into the minor groove of DNA. Fluorescence correlation spectroscopy yields precise dynamic rate constants that prove that the association process of these fluorogenic binders to dsDNA is very similar to that of BBA alone and that their lower affinity is mainly a consequence of their weaker attachment to the minor groove and the resultant faster dissociation process. The conclusions of this study will allow us to go one step further in the design of new DNA binders with tunable fluorescence and binding properties.